Transportation of Critically Ill Patients on Extracorporeal Membrane Oxygenation - Broman, L. Mikael; Frenckner, Björn (Frontiers in Pediatrics, 2016)
Extracorporeal membrane oxygenation (ECMO) may be a life saving procedure for patients with severe reversible pulmonary or cardiac failure or for patients in need for a bridge to transplantation. ECMO is provided by specialized centers, but patients in need of ECMO are frequently taken care of at other centers. Conventional transports to an ECMO center can be hazardous and deaths have been described. For this reason many ECMO centers have developed transport programs with mobile ECMO. After request the mobile team including all necessary equipment to initiate ECMO is sent to the referring hospital, where the patient is cannulated and ECMO commenced. The patient is then transported on ECMO to the ECMO facility by road, helicopter or fixed wing aircraft depending on distance, weather conditions etc. Eight publications have reported series of more than 50 transports on ECMO of which the largest included over 700. Together these papers report on more than 1400 patient transports on ECMO. Two deaths during transport have occurred. A number of other adverse events are described, but without effect on patient outcome. Survival of patients transported on ECMO is equivalent to that of non-transported ECMO patients. It is concluded that long- short-distance interhospital transports on ECMO can be performed safely. The staff should be experienced and highly competent in intensive care, ECMO cannulation, ECMO treatment, intensive care transport and air transport medicine.